Geotechnology and climate change in altitude vegetation (Research, Society and Development, 2021)
Bibliometric analysis is considered a quick and efficient study to assess research trends and academic networks in different research disciplines. The aim of this study was to perform a bibliometric analysis and present an overview of research trends on the spatial and temporal variability of highland vegetation in response to climate change with the aid of geotechnologies. To this end, a bibliographic search was carried out using the Web of Science database on December 11, 2020, to gather academic publications on spatiotemporal changes in altitude vegetation in response to climate change, between the years of 1945 and 2020. A total of 54 publications with aligned abstracts were obtained. All these documents were read and the number of 27 publications that met all the criteria related to the objective of this analysis was reached. The analysis showed that the number of publications related to the topic of this research is still very small and restricted to a few countries and specific vegetation types in certain alpine areas.